Social Exclusion of People with Disability in Bangladesh: Dimensions and Challenges - Muahammed Muazzam Hussain (Asian Social Work Journal, 2021)
This paper is an outcome of reviewing different dimensions of social exclusion and challenges faced by people with disabilities (PWD) in Bangladesh and suggest some policy guidelines to promote inclusion of PWD into the development process. This paper is based on secondary sources of data and therefore, government, non-government organization’s study report, policy documents, journal articles, statistical report, research findings etc. were consulted to collect data and construct the paper. The paper describes the social exclusion of Bangladeshi PWD in the six broad areas e.g. income and assets, employment, education, health and social security, social relationship and recreation. Therefore, some key areas of policy implications are outlined for inclusion of PWD in Bangladesh which include the prospective way to address poverty, adopt active labor market policy, promoting social services and encouraging community based rehabilitation, providing counseling and other support services and utilizing the vision of user involvement etc.